Bahagia dalam Meraih Cita-cita: Kesejahteraan Subjektif Mahasiswa Teknik Arsitektur Ditinjau dari Regulasi Emosi dan Efikasi Diri - Setyani Alfinuha; Fathul Lubabin Nuqul (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2017)
Abstract: Subjective well-being is people’s evaluation of they life. It includes evaluation about cognitive and affective. People have higher subjective well-being, they have a more positive affective or good feelings and satisfied with the life they have. Contrary, people who have lower subjective well-being tend to overcome negative feelings in him. Therefore, subjective well-being is very important in the life of every individual is no exception to the new students. There are many factors that influence the subjective well-being such as sex, religion, education, intelligence emotion regulation and self efficacy. This study focused on the influence of self efficacy and regulasi emosi toward subjective well-being. This study aims to look at the effects of self-efficacy and emotion regulation towards students’s subjective well-being. The study involved 107 new students majoring in engineering architecture that consists of 51 men and 56 women This study uses a quantitative approach which is measured using four scales that is Possitive and Negative Affect Schedule (PANAS) and Satisfaction with Life Scale (SWLS), General Self efficacy (GSE), and Emotion Regulation Questionnaire (ERQ) to measure emotion regulation. The results show that there is the influence of self-efficacy and emotion regulation on subjective well-being. Simultanously, self-efficacy and regulation of emotions influence subjective well-being of 32.5% to the subjective well-being. But partialy, self efficacy more has contribute to subjective well-being, than emotion regulation.Abstrak: Subjective well-being merupakan evaluasi individu terhadap kehidupannya yang meliputi penilaian kognitif dan afeksi. Individu dikatakan memiliki subjective well-being tinggi jika mengalami lebih banyak afeksi positif atau perasaan menyenangkan dan puas atas kehidupan yang dimiliki. Sebaliknya, orang yang memiliki subjective well-being rendah cenderung diliputi perasaan-perasaan negatif dalam dirinya. Oleh sebab itu, subjective well-being sangat penting dalam kehidupan setiap individu tidak terkecuali pada mahasiswa baru. Ada banyak faktor yang mempengaruhi subjective well-being antara lain jenis kelamin, religiusitas, pendidikan, kecerdasan, regulasi emosi dan self efficacy. Penelitian ini memfocuskan tentang pengaruh efikasi diri dan regulasi emosi terhadap subjective well-being. Penelitian ini melibatkan 107 orang mahasiswa baru jurusan teknik arsitektur yang terdiri dari 51 orang laki-laki dan 56 orang perempuan Penelitian ini menggunakan pendekatan kuantitatif yang diukur menggunakan empat skala yaitu Possitive and Negative Affect Schedule (PANAS), Satisfaction with Life Scale (SWLS), General Self efficacy (GSE) dan Emotion Regulation Questionnaire (ERQ). Analisis yang dilakukan adalah analisis deskripsi dan regresi linier berganda. Hasil penelitian menunjukkan bahwa terdapat pengaruh self efficacy dan regulasi emosi terhadap subjective well-being. Secara bersama-sama, self efficacy dan regulasi emosi mempengaruhi subjective well-being sebesar 32,5%terhadap subjective well-being. Secara terpisah, self efficacy memberikan sumbangan sebanyak 21,62% dan regulasi emosi sebanyak 3,53% terhadap subjective well-being.